2012
DOI: 10.1051/0004-6361/201219029
|View full text |Cite
|
Sign up to set email alerts
|

The very low mass multiple system LHS 1070. A testbed for model atmospheres for the lower end of the main sequence

Abstract: Context. LHS 1070 is a nearby multiple system of low mass stars. It is an important source of information for probing the low mass end of the main sequence, down to the hydrogen-burning limit. The primary of the system is a mid-M dwarf and two components are late-M to early L dwarfs, at the star-brown dwarf transition. Hence LHS 1070 is a valuable object to understand the onset of dust formation in cool stellar atmospheres. Aims. This work aims at determining the fundamental stellar parameters of LHS 1070 and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 70 publications
(124 reference statements)
0
20
0
Order By: Relevance
“…These grains produce a "veiling" by dust scattering over the optical band of the latest type M dwarfs. The BT-Settl models use therefore a slightly revised version of the Rossow (1978) cloud model (see Allard et al 2012a,b;Rajpurohit et al 2012b), for details on the model construction.…”
Section: Model Atmospheresmentioning
confidence: 99%
“…These grains produce a "veiling" by dust scattering over the optical band of the latest type M dwarfs. The BT-Settl models use therefore a slightly revised version of the Rossow (1978) cloud model (see Allard et al 2012a,b;Rajpurohit et al 2012b), for details on the model construction.…”
Section: Model Atmospheresmentioning
confidence: 99%
“…Over the last decades tremendous development in the model atmospheres of cool low-mass stars, in particular M-dwarfs, has been achieved (Brott & Hauschildt 2005;Helling et al 2008;Allard et al 2012Allard et al , 2013) that has boosted the number of studies deriving accurate physical parameters of these stars both in the optical and in the near-infrared (Bayo et al 2011(Bayo et al , 2012Rajpurohit et al 2012Rajpurohit et al , 2013Neves et al 2014). Bayo et al (2014) have shown the differences between estimating the parameters in the optical and in the near-infrared, with spectra and photometry.…”
Section: Arxiv:160907062v2 [Astro-phsr] 27 Sep 2016mentioning
confidence: 99%
“…The synthetic spectra were distributed with resolution of R 200 000 via the PHOENIX web simulator 2 and are fully described in Allard et al (2012); Rajpurohit et al (2012) and Allard et al (2013). Oxide bands, which are stronger in M-dwarf spectra, are weaker in the subdwarfs where the hydride bands dominate.…”
Section: Models and Synthetic Spectramentioning
confidence: 99%
“…For more details of the BT-Sett model atmosphere see Allard et al (2012Allard et al ( , 2013 and Rajpurohit et al (2012). The synthetic colours and spectra were distributed with a resolution of around R = 100 000 via the PHOENIX web simulator 2 .…”
Section: Model Atmospheresmentioning
confidence: 99%